1995
DOI: 10.1159/000126982
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Activation of the Hypothalamo-Pituitary-Adrenal Axis by Electrical Stimulation of the Noradrenergic A1 Group Is Not Mediated by Noradrenaline

Abstract: The paraventricular nucleus (PVN) of the hypothalamus, where the CRF-containing neurosecretory cells controlling the hypothalamo-pituitary-adrenal (HPA) axis are located, receives a dense noradrenergic innervation from the A1 group of the caudal ventrolateral medulla. In the present study we studied the relationship between release of noradrenaline (NA) in the PVN and activation of the HPA axis in response to electrical stimulation of the A1 region. In the urethane-anesthetized male rat, extracellular NA in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Other cells in the A2 region also display Fos-like immunoreactivity following i.c.v. LPS injection, and the neurochemical identity of these other neurons needs to be ascertained as various neurotransmitter systems coexist here alongside the noradrenergic neurons [56]. Our results confirm previous findings by Li et a.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other cells in the A2 region also display Fos-like immunoreactivity following i.c.v. LPS injection, and the neurochemical identity of these other neurons needs to be ascertained as various neurotransmitter systems coexist here alongside the noradrenergic neurons [56]. Our results confirm previous findings by Li et a.…”
Section: Discussionsupporting
confidence: 90%
“…Such gross lesioning studies may also damage other fiber tracts originating in the NTS and hence the specific effects of removal of noradrenaline cannot be fully determined. Indeed, the noradrenergic neurons themselves possess additional transmitters [56]and it is possible that these rather than noradrenaline itself are the mediators of A2 effects on the HPA axis. Noradrenaline depletion reduces the Fos response of the PVN to IL-1β [13]as do knife cuts to the ascending projections from the brainstem to the PVN, but these knife cuts do not alter the numbers of Fos-positive cells seen in the region of the NTS, whereas foot shock following such lesions leads to a decrease in the Fos within the NTS but not the PVN [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the periphery, ATP is known to function as a cotransmitter with NE in a number of tissues innervated by the sympathetic system (Burnstock, 1990;von Kugelgen and Starke, 1991). Central noradrenergic neurons might be expected to use similar cotransmission, especially as more evidence accumulates for the involvement of nonadrenergic neurotransmission (Gartside et al, 1995).In the present investigation, perifused explants of the rat hypothalamoneurohypophyseal system (HNS) were used to study the role of ATP and NE in the regulation of VP and oxytocin release. Specifically, the effects of ␣ 1 -adrenergic and purinergic receptor activation and the interactions of these agents were evaluated.…”
mentioning
confidence: 99%
“…We have also demonstrated that the administration of both ionotropic receptor antagonists attenuated the neuroendocrine responses following VNAB and DRN stimulation in a dose-dependent manner. It was previously reported that electrical stimulation of either the VNAB or the DRN caused the release of NE and 5-HT, respectively, in the hypothalamus [24, 25, 26]. Importantly, in the present study the animals were anesthetized with pentobarbital which may enhance GABAergic inhibition and modify the neuroendocrine responses.…”
Section: Discussionmentioning
confidence: 79%